Pheromone synthesis. Part 262: Determination of the absolute configuration of the female sex pheromone [(1S, 2S)-(−)-(1, 2-dimethyl-3-methylenecyclopentyl) acetaldehyde] of the pineapple mealybug (Dysmicoccus brevipes) by synthesis coupled with X-ray analysis. Issue 46 (16th November 2017) - Mori, Kenji; Tabata, Jun
Abstract: The enantiomers of ( anti -1, 2-dimethyl-3-methylenecyclopentyl)acetaldehyde, one of which is the female sex pheromone of the pineapple mealybug ( Dysmicoccus brevipes ), were synthesized. Chirality was introduced by means of lipase-catalyzed asymmetric acetylation of (±)-2, 3-dimethyl-2-cyclopenten-l-ol. X-ray analysis of (−)-camphanate ester of (1 S, 2 S )-(−)-2-(1, 2-dimethyl-3-methylenecyclopentyl)ethanol confirmed its (1 S, 2 S )-absolute configuration. The natural pheromone was identified with the (1 S, 2 S )-aldehyde by comparing the specific rotation, enantioselective GC retention time and pheromone activity. Graphical abstract: